APLIKASI DATAMINING UNTUK MEMPREDIKSI TINGKAT KELULUSAN MAHASISWA MENGGUNAKAN ALGORITMA APRIORI DI IBI DARMAJAYA BANDAR LAMPUNG - -, Nurjoko; Kurniawan, Hendra (244-5567)
The rapid growth of data accumulation has created conditions data-rich but minimal information. Data mining is a mining or the discovery of new information by looking for patterns or particular rules of a number of large amounts of data are expected to tackle the condition. By leveraging master data and data graduation student, is expected to yield information about the graduation rate of students with master data through data mining techniques. Categories graduation rate is measured from the time of study and GPA. The algorithm used is the a priori algorithm, the value of the information displayed in the form of support and confidence from each category graduation rates.Keywords: data mining, algorithms priori, graduation rates, support, confidence